Estimating the value of water-use efficiency in the intermountain west - Groves, David G.; Griffin, James M.; Hajiamiri, Sara.; Environment, Energy, and Economic Development Program (Rand Corporation); Rand Infrastructure, Safety, and Environment (Organization); Rand Corporation; William & Flora Hewlett Foundation (Santa Monica, CA : RAND, 2008)
Evaluating the cost-effectiveness of water-efficiency programs can be difficult, because not all the benefits are easily quantified. This report presents an economic framework based on two tools from the California Urban Water Conservation Council to estimate the avoided costs and environmental benefits of an agency's efficiency programs. The report evaluates the benefits of Denver Water efficiency programs and uses an exploratory modeling approach to accommodate the significant uncertainty in such estimations. The results of this study suggest that the inclusion of long-run avoided costs and environmental benefits is critical to fully recognizing the value of water-use efficiency programs. The authors find that evaluating only the short-run avoided costs leads to the conclusion that many water-efficiency projects already a part of Denver Water's 10-year conservation plan are not cost-effective. When long-run avoided costs and environmental and recreational benefits were factored in, all but two Denver Water programs were estimated to be cost-effective. The timing of projected water savings from efficiency programs is also critical. Water savings from programs that concentrate savings during summer months, when water is scarcer, should be valued higher than saving from programs that lead to more uniform water savings throughout the year, because these water savings reduce peak water needs.
Introduction -- Denver Water Case Study -- Case-Study Methodology -- Results -- Summary and Conclusions -- Appendix A: Avoided-Cost Model -- Appendix B: Environmental-Benefit Modeling -- Appendix C: Impact of Supply and Demand Changes on Long-Run Avoided Costs -- Appendix D: Efficiency-Program Cost Estimates.
"A RAND Infrastructure, Safety, and Environment Program."
"RAND Environment, Energy, and Economic Development."
"The research described in this report was conducted under the auspices of the Environment, Energy, and Economic Development Program (EEED) within RAND Infrastructure, Safety, and Environment (ISE)"--Title page verso.
Includes bibliographical references (p. 67-69).
Also available on the internet via WWW in PDF format.
Keywords: Water conservation -- Colorado -- Denver -- Case studies; Water conservation -- Colorado -- Denver -- Econometric models; Water efficiency -- Economic aspects -- Colorado -- Denver -- Case studies; Water efficiency -- Economic aspects -- Colorado -- Denver -- Econometric models; Water supply -- Colorado -- Denver -- Case studies; Water supply -- Colorado -- Denver -- Econometric models